Efektivitas Pendekatan Rational Emotive Behavior Therapy Setting Kelompok untuk Meningkatkan Kontrol Diri Siswa dalam Pencegahan Penyalahgunaan Narkoba - Hidayat, Rahmat; Karneli, Yeni (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2022)
Drug abuse is a negative/irrational behavior that can harm oneself and others. One of the causes of drug abuse is the low self-control of students. Clients who have problems with low self-control in drug abuse need to be counseled through rational emotive behavior therapy in group settings. The aims of this study were: (1) to test the significant difference in the level of self-control of the experimental group students before and after being given the rational emotive behavior therapy setting technique, (2) to test the significant difference in the level of self-control of the control group students before and after being given services without treatment specifically, (3) examine the effectiveness of the rational approach to emotive behavior therapy setting in groups in increasing self-control in preventing drug abuse. This study used a quasi-experimental non-equivalent control group design with pretest and posttest. The research subjects were students of class VIII-3 and VIII-4 at SMP Negeri 4 Padang Pariaman with a sample of 20 people who were divided into 2 groups consisting of 10 people as the experimental group and 10 people as the control group. The sampling technique was purposive sampling technique. Data were analyzed using the Wilcoxon signed Rank Test and Kolmogorov Smirnov 2 Independent Samples with the help of SPSS version 20. The results showed that the rational emotive behavior threapy approach was effective in increasing students' self-control in preventing drug abuse. This can be seen from: (1) there is a significant difference in the level of self-control of the experimental group students before and after being given the rational emotive behavior therapy setting technique, (2) there is a significant difference in the level of self-control of the control group students before and after being given services without treatment specifically, (3) there is the effectiveness of the rational approach to emotive behavior therapy setting in groups in increasing self-control in preventing drug abuse. The implementation of the rational emotive behavior therapy setting approach in groups should be intensified in the form of Guidance Counseling programs and designed as well as possible by counsellors or Guidance Counseling teachers.